Domestic violence and abuse in gay and bisexual men attending a sexual health clinic: pilot testing of an educational support intervention for sexual health practitioners. (13th November 2015) - Bacchus, Loraine J; Buller, Ana Maria; Ferrari, Guilia; Peters, Tim; Devries, Karen; Sethi, Gulshan; White, John; Hester, Marianne; Brzank, Petra J; Feder, Gene S
Abstract: Background: Domestic violence and abuse is recognised globally as a pervasive public health issue, but there is less research in relation to gay and bisexual men. This study aimed to measure the occurrence of negative and potentially abusive behaviour and associations with health problems in gay and bisexual men; and pilot test an educational intervention for practitioners to increase awareness of domestic violence and abuse and provide skills in inquiry and support. Methods: Between Sept 21, 2010, and May 25, 2011, an anonymous Health and Relationships survey was administered to English-literate men (aged 18 years) attending a sexual health clinic in London, UK. Negative behaviour included: feeling frightened of the behaviour of a partner; having to ask permission (beyond being considerate to and checking with a partner); being slapped, hit, kicked, or physically hurt; and forced sex or sexual activity. Health problems included mental health, sexual health, and alcohol and illicit drug use. Sexual health practitioners received training on the educational intervention HERMES (HEalthcare Responding to MEn for Safety). 6 weeks after training, 21 semi-structured interviews were conducted with the practitioners to assess acceptability of HERMES, changes in awareness, and confidence in identifying and responding to gay and bisexual men who were experiencing domestic violence and abuse. Findings: Of 2657 men who attended the clinic, 1132 (42·4%) completed the survey. 532 (47·2%) self-identified as gay or bisexual. 33·9% (95% CI 24·9–37·9) of gay and bisexual men reported ever experiencing a negative and potentially abusive behaviour from a partner. Ever being frightened by a partner and having to ask a partner's permission were associated with increased odds of being anxious (odds ratio [OR] 2·5, 95% CI 2·0–3·1 and 2·7, 1·6–4·7, respectively). Being frightened of a partner, being physically hurt, and physically hurting a partner were associated with increased odds of using a class A drug in the previous 12 months (OR 2·2, 1·5–3·2; 2·3, 1·4–3·8; and 3·1, 2·3–4·2, respectively). Practitioners welcomed HERMES and felt that it raised their awareness and confidence in dealing with domestic violence and abuse among gay and bisexual men. Interpretation: In this clinical setting the occurrence of potentially abusive behaviours in gay and bisexual men was high. HERMES increased sexual health practitioners' awareness of domestic violence and abuse and confidence in asking about abuse. The results can only be interpreted within the context of the sexual health clinic. Because of the cross-sectional design, it is not possible to determine the temporal direction of the associations between negative behaviour and health problems. Funding: This report presents independent research commissioned by the National Institute for Health Research (NIHR) under its Programme Grants for Applied Research scheme (RP-PG-0108-10084).